THE ROLE OF THE FAMILY IN FORMING HEALTHY LIFESTYLE OF CHILDREN OF PRESCHOOL AGE - Светлана Николаевна Виниченко; Нина Константиновна Перевощикова; Светлана Альбертовна Дракина; Наталья Степановна Черных (The Publishing House Medicine and Enlightenment, 2017)
Family is an important part of socialization of the child, and the process of formation of health depends not only on the family's financial situation, social status and parental education, but also on their value orientations, the depths of the paternal and maternal feelings, understanding parental duty, desire and the desire to work with children, educate and train them. Goal - evaluation of the influence of family on forming of healthy lifestyle of children of preschool age. Materials and methods. The study involved 116 children who were divided into three groups: one group comprised children attending swimming lessons twice a week (n = 54); the second group of children (n = 30) engaged in other sports (dancing, wrestling, football, hockey); the third group (n = 32) children not attending sports clubs. There was evaluated the state of health of children and psychological characteristics (test anxiety Tamela R., Amen V., Dorcy M. «Select the desired entity»), the quality of life for Tsybulskaya I.S., analysis of family relationships according to Eidemiller E.G., Justices V.V. The results of the study. Parent's attitude to the sport was different in all groups. The parents were not engaged in physical culture regularly (at least 1 time per week) - 38 % of mothers and 36 % fathers in the first group, 43 % of mothers and 46 % of the fathers of the second group and 90.5 % of mothers (p = 0,0086) and 76 % of fathers (p = 0,0089) in the group of children not involved in sports. In the evaluation of physical development was noted significantly more excess body weight, children had 3 groups (21,88 % against 7.4 % in the first and 7.67 per cent in the second, p = 0,0394). The incidence of statistically significantly more frequently recorded diseases of the nervous system and the respiratory system in the group of children with low physical activity. In the evaluation of mental health revealed that among children not involved in sports more often were diagnosed with low anxiety level, quality of life and pathological style of parent-child relationships. Conclusions. Family relationships are closely intertwined with the socio-economic characteristics of the family, and the result of the assessment is the child's health.